TAFSIR TEMATIK KEMENAG: STUDI AL-QURAN DAN PENDIDIKAN ANAK USIA DINI - Atik Wartini (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2016)
This research is based on library research. In this study wanted to discuss the theme of the Qur'an and Early Childhood Education son, al-Qur’an as a source and a philosophy of life, in this study there are three questions how the Koran speaks of early childhood education , secondly, how the education of children in the family, using content analysis the authors tried to find in depth on the theme of early childhood education in the verses of the Qur'an, so the results of his research is the first, the child knows the concept of early childhood education in al-Qur 'an, both knowing pendidikana children in the family.